Environmental temperature: composition and conformation of the carcasses of pre-ruminant kid goats and lambs - Sanz M.R.; Prieto I.; Gil F.; Fonolla J. (Body condition of sheep and goats: Methodological aspects and applications, 1995)
In order to quantify the effect of environmental temperature on the composition and conformation of the carcasses of pre-ruminant kid goats and lambs, a series of trials have been performed using such animals housed at different temperatures (12, 24 and 30 degrees C). These animals were fed ad libitum with a milk replacer, from birth until two months of age. Taking into account the different food intake rates and the differences in the utilization of the feed ingested in the different species as a function of temperature, no significant differences in growth rate were observed in the different species. The composition expressed as a function of the empty-body-weight and the carcass composition of kids was affected by temperature only to the extent that the final composition was affected by temperature, independently of the live weight achieved. Finally, despite the comments already made, the kids kept at the lowest temperature had carcasses with a better conformation.
Seminar of the Working Group on Body Condition of Sheep and Goats of the FAO/CIHEAM Network on Sheep and Goats, 24-31 Mar 1994, Zaragoza (Spain)